Ekstraksi Kurkumin Dari Rimpang Kunyit (Curcuma Longa) Sebagai Pewarna Alami Pada Komestik Blush On Menggunakan Pelarut Ethanol - Artikanabila, Cut; Diana, Selvie; Dewi, Ratni (Politeknik Negeri Lhokseumawe, 2023)
Turmeric contains chemicals that are benefical for the health of the body and can be used for making cosmetics. This study aims to make blush on cosmetics from natural ingredients with some benefits that not only increase external beauty but also nourish the skin from within by utilizing the natural color of the turmeric plant. Turmeric extraction was carried out using ethanol as a solvent using the maceration method. Maseration is done for 3x24 hours. This study used variations in the concentration of turmeric extract as mush as 4ml, 6ml, 8ml and 10ml with variations in the concentration of talcum as much as 0gr, 0.5gr, 1gr, 1.5gr and 2gr. The testing that has done includes flavonoid test, pH values, irritation test and organoleptic test. The results of this study showed us that the best blush on with a composition of 8ml turmeric extract with 0.5gr talc has a positive flavonoid value, a pH value is 4.9 compatiable according to the pH of face skin, which 4.6-7, an irritation test value of 0 indicates that the blush on does not irritate the skin and the organoleptic test results have an average color value of 4.2, and average aroma of 4.3 and an average texture of 4.0.